Detecção do Paracoccidioides spp. em amostras ambientais e diferenciação do complexo P. brasiliensis da espécie P. lutzii por Nested PCR e hibridização in situ - Arantes, Thales Domingos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Soil is probably the habitat of pathogenic fungi Paracoccidioides spp., due to the molecular detection of this pathogen in these samples, associated with the frequent of infection in rural workers and the isolation in wild animals (Dasypus novemcinctus and Cabassous centralis). This project aimed to detect and differentiate the species P. brasiliensis (complex) and P. lutzii in the environment, by the techniques of Nested PCR and FISH, respectively, in environmental aerosol samples and soil from armadillo's burrows, from endemic and non-endemic areas to Paracoccidioidomycosis in the Southeast, Midwest and North regions of Brazil. Besides the environmental detection of Paracoccidioides spp. by molecular methods, the occurrence of armadillos infected with P. lutzii the Brazilian center-west region with the highest prevalence of this kind, where no animals were evaluated at the present time will be studied. We achieved positive detection of both species of Paracoccidioides by both detection techniques (PCR and in situ hybridization), and further the differentiation by the ITS (Internal Transcribed Spacer) we could visualize fungal species in some aerosol samples also differentiating the two species. We believe of the data reflect the actual occurrence of fungi in their niche, however the animal isolation in armadillo's showed up negative for 7 animals evaluated at work, which indicated that the ratio of the species P. lutzii with armadillo may not be the same with cases of armadillo's infected with P. brasiliensis in other regions of Brazil

O solo é o provável habitat do fungo patogênico Paracoccidioides spp., devido à detecção molecular deste patógeno neste tipo de amostra, associada à frequente infecção de trabalhadores rurais e isolamento em animais silvestres (Dasypus novemcinctus e Cabassous centralis). O presente estudo visou detectar e diferenciar as espécies Paracoccidioides brasiliensis (complexo) e Paracoccidioides lutzii no ambiente, pelas técnicas de Nested PCR, FISH, respectivamente, em amostras ambientais aerossóis e solo de tocas de tatus provenientes de áreas endêmicas para a Paracoccidioidomicose nas regiões Sudeste, Centro-Oeste e Norte brasileiras. Além da detecção ambiental de Paracoccidioides sp. por métodos moleculares, foi estudada a ocorrência de tatus infectados com P. lutzii no centro-oeste brasileiro, região de maior prevalência desta espécie, onde nenhum animal havia sido avaliado até o presente momento. Obtivemos a detecção positiva para ambas as espécies de Paracoccidioides por ambas as técnicas de detecção (Nested PCR e hibridização in situ), além da diferenciação por ITS (Internal Transcribed Spacer) pudemos visualizar os espécimes fúngicos em algumas amostras aerossóis. Acreditamos que os dados refletem a real ocorrência dos fungos em seu nicho, no entanto, o isolamento animal em tatus demonstrou-se negativo para 7 animais avaliados no trabalho, o que pode indicar que a relação da espécie P. lutzii com os tatus pode não ser a mesma com os casos de tatus infectados com P. brasiliensis em outras regiões brasileiras
Keywords: Paracoccidioides brasiliensis; Reação em cadeia da polimerase; Hibridização in situ; Fungos do solo; In situ hybridization